2005
DOI: 10.1080/01468030590966553
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a Grating-Folded Optical Directional Coupler

Abstract: We developed a new optical add/drop multiplexer composed only of a grating-folded directional coupler. We found that in this multiplexer, the power drop becomes maximal when the grating-coupling strength is equal to that of directional coupling. At this maximum power, both power transfer between the waveguides and power reflection take place simultaneously at the grating. The power drop approaches 1 when the grating length increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…It has recently been shown [3,7,8] that the numeric solution of an MI constructed with a directional coupler followed by Bragg gratings in the two output arms constitutes an all-optical interferometer applied to telecommunications systems [7,9]. Based on those characteristics, the objective here it to study MIs working as a multiplexer add-drop filter.…”
Section: Theoretical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown [3,7,8] that the numeric solution of an MI constructed with a directional coupler followed by Bragg gratings in the two output arms constitutes an all-optical interferometer applied to telecommunications systems [7,9]. Based on those characteristics, the objective here it to study MIs working as a multiplexer add-drop filter.…”
Section: Theoretical Proceduresmentioning
confidence: 99%
“…The analysis of this device requests the solution of the transfer matrix, and it is complicated by the fact that the coupling and reflections exist simultaneously in a certain region of the device. The analysis of the MI is easier, since the regions of the coupling are separate from the Bragg grating, as shown in Figure 1, [8][9][10]. It is shown that this picture can be applied to the device as a coupler followed by a Bragg grating, and the analysis is considerably simple.…”
Section: Introductionmentioning
confidence: 94%
“…The Add-Drop Multiplexer (ADM) is one of the key components for dense wavelengthdivision multiplexing (DWDM) systems (Murakami 2005;Kobayashi et al 2007;Baumann et al 1996). In the emerging next-generation transport networks, called intelligent optical networks, WDM-based optical components such as add-drop multiplexers (ADMs) and optical cross-connects (OXCs) will have full knowledge of the wavelengths in the network, status, and traffic-carrying capacity of each wavelength (Ilyas and Mouftah 2003).…”
Section: Optical Add-drop Multiplexersmentioning
confidence: 99%
“…All optical telecommunication networks with high transmission capability, based on optical time division multiplexed (OTDM) and wavelength-division multiplexing (WDM) systems requires stable and compact switching devices for ultrahigh-speed demultiplexing and add/drop multiplexing (Kawanishi 1996;Hess et al 1998;Murakami 2005). Desired features include bit-rate and wavelength flexibility, low fibre-to-fibre losses, and a large dynamic range.…”
Section: Introductionmentioning
confidence: 99%
“…where Λ is the grating period, n eff is the effective index and N is the order of Bragg [9][10][11][12][13].…”
Section: Fiber Bragg Gratingmentioning
confidence: 99%